Tracing biomimicry from the ancient Chinese wisdom: a case study at Lushan UNESCO Global Geopark - Lyuxin Xiong; Mazlan Mohd Tahir; Tanot Anak Unjah; Chao Xu (Journal of Asian Architecture and Building Engineering)
This paper uses the Lushan UNESCO Global Geopark as a sample to explore the application of biomimicry based on ancient Chinese methods. Based on systematic literature on biomimicry terminology and practice, we identify five main approaches borrowed from ancient China. These practices apply to architecture and landscape, including orientation, building planning, and structural design. Emphasis on preserving local knowledge related to genius loci contributes to the sense of place of UNESCO Geoparks. The Lushan UNESCO Global Geopark is an architectural sample of the application of this approach. According to the sample, ancient Chinese biomimicry closely linked itself to its environment by using nature as a model, understanding the meaning of nature and interpreting topography and climate; discovering the laws of nature and using methods that take advantage of natural conditions, and realizing techniques for the harmonious coexistence of architecture and the site’s environment.